Improvement of the anonymity formalization based on strand space model - DONG Xue-wen1; NIU Wen-sheng2; MA Jian-feng1; XIE Hui1; MAO Li-qiang1 (Tongxin xuebao)
In order to make the strand space model satisfy the special needs of anonymity analysis,based on equivalent bundles and view of observer,two kinds of sender anonymities as well as recipient anonymities were defined;relation anonymity were defined in two ways: emphasis on sender anonymity or recipient anonymity.Thus,an anonymity for-malization framework based on strand space model was extended and completed.In addition,the difference among ano-nymity degrees of these anonymities were qualitatively researched and the anonymity of a zone-based k-anonymity rout-ing protocol was analyzed to verify the correctness and efficiency.